Zero Distance Management in the Quantum Age - Zohar, Danah; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2022)
(3z(BWhen Danah Zohar first published the early ideas of her Quantum Management Theory in the late 1990$1 (Bs, she articulated a new paradigm, inspired by quantum physics, and began a major contribution to our search for a new management theory that can replace outdated Taylorism. Now, in ZERO DISTANCE, the most comprehensive account of her project, she outlines how the theory has been implemented through the revolutionary RenDanHeyi business model of China$1 (Bs Haier Group, and subsequently several other large companies. Zohar$1 (Bs suggestion that the Haier model also offers a new social and political model is thought provoking. This book is a significant addition to our continuing conversation about the best way to manage companies and other human social systems. I recommend it highly.(3y (B- Gary Hamel, London Business School, Author of Humanocracy This open access book offers a new management meta-theory to replace Taylorism. It presents a new paradigm in management thinking and a new, practical organizational model for implementing it in our personal and working lives, in our companies, in our communities and nations, and in a sustainable global order. It will offer an understanding of why and how (3z(Bthinking-as-usual(3y (Bis failing both business and political leaders in these new times, and it will advocate new thinking and new management practices that are so radically new that they turn everything we have taken for granted inside out and upside down. This new management model is called (3z(BQuantum Management Theory(3y(B, because it is rooted in the new paradigm bequeathed to us by quantum physics and its younger sibling, complexity science. Danah Zohar is a physicist, philosopher, and management thought leader. She is a Visiting Professor at Tsinghua University$1 (Bs School of Economics and Management and a Visiting Professor at the China Academy of Art.s
Introduction -- Part I: The Building Blocks -- Chap. 1: From the Newtonian Age to the Quantum Age -- Chap. 2: Defining Elements of Quantum Systems -- Chap. 3: What Is Quantum Management? -- Chap. 4: Implementing Quantum Management: RenDanHeyi Business Model -- Chap. 5: The Tao of Quantum Management -- Part II: The Quantum Person/Employee -- Chap. 6: I Am the Universe -- Chap. 7: I Am a Particle & a Wave -- Chap. 8: I Am a Multitude -- Chap. 9: I Make the World -- Chap.10: The Motivations That Drive Me -- Part III: The Quantum Leader -- Chap. 11: A Leader of Leaders -- Chap. 12: Twelve Principles of Quantum Leadership -- Chap. 13: Thinking Principles & Skills of the Quantum Leader -- Part IV: The Quantum Organization -- Chap. 14: What Makes A Quantum Organization? -- Chap. 15: Haier: A Maker$1 (Bs Culture -- Chap. 16: Roche India: A Purpose Driven Culture -- Chap. 17: GE Appliances: An American Catalyst -- Chap. 18: Other Companies Featuring Quantum Management Principles -- Chap.19: US Army Special Operations Task Force: RenDanHeyi for the Military -- Part V: The Quantum Society -- Chap. 20: What Is a Quantum Society? -- Chap. 21: Governing a Quantum Society: Two Great Experiments -- Chap. 22: A Quantum Global Order -- Conclusion: The Quantum World View.s
Keywords: Business; Management science; Asia$1 (BEconomic conditions.s; Business and Management; Asian Economics